(untitled) (Reflection and Critique Law Magazine, 2022)
The present article will analyze the introduction of the interlocking statute of limitations in civil actions for administrative improbity in article 23, §§ 4 to 8 of Law No. 8.429 of 1992, included by Law No. 14.230 of October 25, 2021. The initial intention of the legislator will be investigated, as well as the final wording of the bill that resulted in the inclusion of the statute of limitations among the stages of the process, something that already existed in the Penal Code, but not in the law that defends administrative probity. The doctrine will be consulted to clarify the essence of the statute of limitations. In conclusion, the collegiate decision of the Federal Supreme Court in the judgment of General Repercussion Topic no. 1.199 (ARE 843.989) will be visited, which defined the application of the new periods of general and interlocking prescription.